2011
DOI: 10.1128/jvi.05086-11
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Clade HIV-1 Neutralizing Antibodies Induced with V3-Scaffold Protein Immunogens following Priming with gp120 DNA

Abstract: The V3 epitope is a known target for HIV-1 neutralizing antibodies (NAbs), and V3-scaffold fusion proteins used as boosting immunogens after gp120 DNA priming were previously shown to induce NAbs in rabbits. Here, we evaluated whether the breadth and potency of the NAb response could be improved when boosted with rationally designed V3-scaffold immunogens. Rabbits were primed with codon-optimized clade C gp120 DNA and boosted with one of five V3-cholera toxin B fusion proteins (V3-CTBs) or with double combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 77 publications
2
51
0
Order By: Relevance
“…We had previously tested cholera toxin B subunit (CTB)-based immunogens carrying HIV-1 V3 epitopes and showed that they were highly immunogenic and elicited cross-clade neutralizing Ab responses in rabbits (48)(49)(50). To test CTB's effects on V1V2 immunogens, we chemically conjugated the structurally constrained V1V2(ZM109)-1FD6 with the CTB and showed that it preserved the V2q and V2i epitopes in the V1V2 scaffold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously tested cholera toxin B subunit (CTB)-based immunogens carrying HIV-1 V3 epitopes and showed that they were highly immunogenic and elicited cross-clade neutralizing Ab responses in rabbits (48)(49)(50). To test CTB's effects on V1V2 immunogens, we chemically conjugated the structurally constrained V1V2(ZM109)-1FD6 with the CTB and showed that it preserved the V2q and V2i epitopes in the V1V2 scaffold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This immunogenic region is likely another vulnerable site in V1V2, in addition to the strand C targeted by PG9 and other QNE MAbs. Precise structural mapping of this epitope region provides an opportunity to rationally design scaffold immunogens to focus antibody responses on this region (43,44). One challenge of targeting this epitope region is the flexibility of strand C=, which may render this region less immunogenic than the strand C region.…”
Section: Discussionmentioning
confidence: 99%
“…For this, the V3 loop was spliced into a conformationally correct site on the highly immunogenic protein, cholera toxin subunit B, a protein which forms a pentameric structure and therefore presents five copies of V3 (94), serving as a particularly strong antigen for induction of Abs (95). High anti-V3 Ab titers were elicited in rabbits with one or a combination of V3-cholera toxin subunit B immunogens, and these immune sera were able to neutralize numerous diverse HIV strains (33,94).…”
Section: Abs Targeting Variable Loop 3 (V3)mentioning
confidence: 99%
“…Thus, even though conventional nAbs are limited in their breadth and potency, they are commonly made by HIV-positive individuals (32), by immunized humans (24), and by immunized animals (33,34), and the previously mentioned studies suggest that they can reduce infection rates. Therefore, such Abs, induced by vaccines, have substantial potential for influencing the course of the HIV epidemic.…”
Section: Types Of Antibodies Conventional Absmentioning
confidence: 99%